2019
DOI: 10.1002/anie.201902361
|View full text |Cite
|
Sign up to set email alerts
|

High‐Rate, Tunable Syngas Production with Artificial Photosynthetic Cells

Abstract: An artificial photosynthetic (APS) system consisting of a photoanodic semiconductor that harvests solar photons to split H2O, a Ni‐SNG cathodic catalyst for the dark reaction of CO2 reduction in a CO2‐saturated NaHCO3 solution, and a proton‐conducting membrane enabled syngas production from CO2 and H2O with solar‐to‐syngas energy‐conversion efficiency of up to 13.6 %. The syngas CO/H2 ratio was tunable between 1:2 and 5:1. Integration of the APS system with photovoltaic cells led to an impressive overall quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…5(b) [46], the hydrogen electrode potentials (NHE) of g-C3N4 nanosheets and Co(II)/PCN-2 are determined as −0.67 and −0.53 V versus NHE, which are consistent with reported literatures [47]. Obviously, Co(II)/PCN-2 shows more positive flat-band potential than g-C3N4 nanosheets, which might be caused by the lower overpotential as well as splendid electronic conductivity of Co(II) [48,49].…”
Section: Resultssupporting
confidence: 89%
“…5(b) [46], the hydrogen electrode potentials (NHE) of g-C3N4 nanosheets and Co(II)/PCN-2 are determined as −0.67 and −0.53 V versus NHE, which are consistent with reported literatures [47]. Obviously, Co(II)/PCN-2 shows more positive flat-band potential than g-C3N4 nanosheets, which might be caused by the lower overpotential as well as splendid electronic conductivity of Co(II) [48,49].…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the different numbers of accumulated electrons on the reactive sites will lead to different pathways, and final products. Zhang et al investigated this factor of single Ni atoms and explored the collection and localization of electrons by electrochemical microscopy‐atomic force microscopy (SECM‐AFM). Results showed that the single nickel atom sites have a uniform capacity of electron storage, Figure 5 .…”
Section: Single Atomsmentioning
confidence: 99%
“…d) Current‐responsive image of Ni‐SNG reference with corresponding line profiles of topography and current. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Single Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency is higher than recently reported values in a PEC cell without external bias ( Li et al., 2019 ; Andrei et al., 2020 ). Although the efficiency is lower than that reported in photovoltaic-electrolysis (PV-E) system ( Schreier et al., 2015a , 2017 ; Urbain et al., 2017 ; Zhang et al., 2019 ; Kim et al., 2019 ; Cheng et al., 2020 ), the PEC approach integrates the light harvesting and electrochemical process of PV-E process into a single and monolithic device via a direct semiconductor-electrolyte interface, providing potential advantages over the PV-E system in terms of cost and complexity. And it is expected that the STS efficiency of the PEC system could be enhanced further by employing better photoanode with higher photocurrent at the low bias region, which would improve the overlap of J-V curves between photocathode and photoanode.…”
Section: Resultsmentioning
confidence: 98%